Comparative analysis of metabolic risks and related non-communicable disease burden across sociodemographic index regions from 1990 to 2021 - Shiwei Sun; Jingjing Duan; Ziwei Liu; Xiude Fan; Zinuo Yuan; Yongfeng Song; Chunhui Ding (BMJ Open)
Objective To analyse the trends and differences of metabolic risks related non-communicable diseases (NCDs) globally and across various sociodemographic index (SDI) regions from 1990 to 2021.Design Observational study.Setting The data of global and all SDI regions were obtained from the Global Burden of Disease Study 2021 database.Main outcome measures Age-standardised deaths rate and disability-adjusted life-years (DALYs) percentage of NCDs attributable to metabolic risk were analysed worldwide and across SDI regions from 1990 to 2021. Besides, we analysed the regional trends of metabolic risk summary exposure value (SEV). A detailed analysis of the specific disease burden of various body systems caused by metabolic risks was also provided.Results From 1990 to 2021, all regions showed increased SEV for metabolic risks, with the most notable growth in middle (total change: +84.8%, 95% uncertainty intervals (95% UI) 72.6% to 96.0%) and low-middle SDI regions (+84.5%, 95% UI 70.5% to 95.5%). While high SDI regions had the highest SEV (29.916 in 2021, 95% UI 26.968 to 32.237), they experienced significant reductions in mortality (−49.6%, 95% UI –53.5% to −46.2%) attributable to metabolic risks. DALYs associated with metabolic risks, particularly high body mass index (HBMI), increased notably, especially in less-developed regions (DALYs of NCDs due to HBMI in low-middle SDI regions: +99.9%, 95% UI 76.4% to 114.5%). In these areas, notable DALY rises were observed for conditions including cardiovascular diseases, digestive diseases and particularly metabolic risk-related cancers (>80.0%), reflecting a distinctive shift in the distribution of NCD burdens related to metabolic risks.Conclusions The rising metabolic risk exposure and associated NCD burden, particularly in less developed regions, underscores the need for targeted public health interventions to mitigate these growing health challenges.